A three-phased model to support the design and development of core competency education for liaison mental health clinicians. Issue 3 (6th April 2021) - Lamph, Gary; Bullen-Foster, Claire
Abstract : Purpose: This paper aims to provide an insight into the design, development and delivery proposals for a first of its kind "Liaison Mental Health Training Programme". In the UK, there has been a significant investment in Liaison Mental Health Services and an expansion of the workforce (NHS England, 2016). However, the complexity and varied presentations of patients who attend to acute physical health services now requires a dedicated strategy to address any skills deficit in the mental health liaison workforce and to support core competency development (DOH, 2016). Design/methodology/approach: This paper provides an overview of preparations to develop a regional educational pilot programme using a three-phased model: Phase 1 – Review of policy and best practice guidelines; Phase 2 – Stakeholder Data Collection; and Phase 3 – Synthesis and Development. Findings: An insight into the developmental processes undertaken to shape a core competency liaison mental health training programme is presented. Additionally, the authors provide insight into educational theory and an overview of the LMH Core Competency Curricula. Practical implications: This paper provides the reader with an insight into our findings and a focussed core competency training model for those working within LMH services. This programme development was reviewed throughout by both those using LMH services and the LMH practitioners working within them, ensuring the curriculum proposed was endorsed by key stakeholders. The three-phased model has transferable benefits to other training development initiatives. Originality/value: To the best of the authors' knowledge, this training is the first of its kind in the UK and addresses the education of essential core competencies of a regional liaison mental health workforce. The collaboration of clinical and academic expertise and model of co-production makes this endeavour unique.